THE ROLE OF THE NURSING TEAM IN CARDIORRESPIRATORY STOP IN INTENSIVE THERAPY UNIT AN INTEGRATING LITERATURE REVIEW: AN INTEGRATING LITERATURE REVIEW (CIPEEX, 2022)
INTRODUCTION: THE CARDIORESPIRATORY STOP (CRP) IS DEFINED AS THE SUDDEN CESSATION OF USEFUL VENTRICULARMYOCARDIAL ACTIVITY, ASSOCIATED WITH LACK OF BREATHING, AND HAS NOT RECEIVED DUE ATTENTION FROM THE HEALTH TEAM.IT IS AN EVENT THAT OCCURS FREQUENTLY IN THE ICU, SINCE THESE UNITS ASSIST SEVERELY ILL PATIENTS WITH MARKEDHEMODYNAMIC INSTABILITY, REQUIRING THE TEAM TO IMPROVE THEIR COGNITIVE, MOTOR SKILLS AND UPDATE ON RESUSCITATIONMANEUVERS (FERREIRA ET AL., 2012 ). IN ORDER FOR CARE TO HAPPEN PROPERLY, QUICKLY AND SAFELY, THEMULTIPROFESSIONAL TEAM MUST BE PREPARED TO ENSURE SUCCESS. IN ADDITION, CRP REQUIRES PROMPT ASSISTANCE TOAVOID INJURY AND BETTER PATIENT RECOVERY. THE QUALITY OF CARE ALLOWS FOR PREVENTION AND UNDESIRABLE EVENTS,WHICH MAY COMPROMISE THE PATIENT'S HEALTH (MOURA ET AL., 2012). OBJECTIVE: THE OBJECTIVE OF THIS STUDY WASTO DEMONSTRATE THE IMPORTANCE OF NURSING CARE IN AN EMERGENCY SITUATION TO THE PATIENT VICTIM OFCARDIORESPIRATORY ARREST AT THE INTENSIVE CARE UNIT THROUGH THE LITERATURE. METHOD: THIS IS AN INTEGRATIVEREVIEW OF THE LITERATURE. WITH THE PURPOSE OF GATHERING, ANALYZING AND SYNTHESIZING EXISTING STUDIES ON THEPROPOSED THEME. FOR THE DEVELOPMENT OF THE STUDY, THE SEARCH FOR ORIGINAL SCIENTIFIC ARTICLES PUBLISHED IN THEDATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), MEDICAL LITERATURE ANALYSISAND RETRIEVAL SYSTEM ONLINE (MEDLINE), PUBMED CENTRAL, SIX YEARS (2011-2015), AVAILABLE IN FULL INPORTUGUESE, ENGLISH AND SPANISH. THE DESCRIPTORS IN HEALTH SCIENCES (DECS) WERE USED: PCR, NURSING CARE;ICU. INCLUDED IN THE INTEGRATIVE REVIEW WERE STUDIES THAT OBEYED THE FOLLOWING CRITERIA: ARTICLES THAT PRESENT THECONCEPT OR DEFINITION ADOPTED FOR CARDIOPULMONARY ARREST IN BRAZIL, WHERE THE CHARACTERISTICS OF THE SAMPLE ARECLEAR, AS WELL AS THE COUNTRY, CITY AND HOSPITAL SECTOR IN THAT DATA COLLECTION HAS OCCURRED. THEN, THE FIVEMETHODOLOGICAL MOMENTS OF EXECUTION WERE CARRIED OUT ACCORDING TO MENDES (2008), DETERMINATION OF THEGUIDING QUESTION, EXPLORATORY READING, READING COMPREHENSION AND ANALYSIS AND CONTENT ANALYSIS. 6 ARTICLESWERE SELECTED. RESULTS: AFTER THE ANALYSIS OF CONTENT EMERGED THE CATEGORIES: PROCEDURES RECOMMENDED INTHE SERVICE OF PCR; KNOWLEDGE AND DIFFICULTIES FOUND BY THE NURSING TEAM. OF CATEGORY II APPEARED TWOSUBCATEGORIES BEING THESE: SUBCATEGORY I - KNOWLEDGE OF THE TEAM AGAINST THE PCR; SUBCATEGORY II -DIFFICULTIES FOUND BY NURSING PROFESSIONALS. CONCLUSION: THE RESULTS OBTAINED AFTER THE ANALYSIS SHOWEDTHAT THE DETERMINANTS OF THE SURVIVAL OF THE VICTIMS OF CRP ARE KNOWLEDGE OF THE HEALTH PROFESSIONAL, RELATED TOTHE BASIC LIFE SUPPORT AND ADVANCED LIFE SUPPORT, THE THEORETICAL-PRACTICAL KNOWLEDGE OF THE NURSE ABOUT THEMANEUVERS AND THE EARLY DIAGNOSIS OF CARDIORESPIRATORY ARREST. IT IS NECESSARY THAT THE NURSE PARTICIPATES INTRAINING AND UPDATES AND THAT THERE ARE INVESTMENTS IN THEIR KNOWLEDGE, BECAUSE THE POSITIVE RESULT CAN SAVELIVES.
Keywords: Cardiopulmonary arrest. ICU. Nursing Assistance.